Römische Orationen: zur neueren Übersetzungsgeschichte - Stock, Alex (Zeitschrift für katholische Theologie, 1999)
This article deals with the current discussion on the translations of the 'Latin mass orations'. It tries to show the importance of very accurate translations in order to enrich our own religious language. General questions are discussed by examples.